(untitled) (Experimental biology, 2015)
As a result of 13 years of research revealed the floristic composition of gully and oak woods. Flora is represented by 509 species of plants belonging to 73 families and 292 genera. When this was a decrease in species diversity due to the impact of various environmental factors. The disappearances of 55 species have led to a reduction in the natural gene pool and reduce productivity of natural floodplain and riparian vegetation. The most common types of oak woods are oak forests -Blackberry and oak forests - Convallaria. Currently, there is degradation of oak. Reasons caused by this process are: air pollution, water level drop of Ural River, the groundwater level, mass diseases of trees and leaf mass destruction by pests and climatic changes. Keywords: oak forest, environmental factors